Cultural Discourse on Human Rights- An Indian Perspective : Array - VijayaKumar, Sindhu (Acta Universitatis Danubius. Relationes Internationales, 2021)
Bharat the land of holistic culture has always given importance to life and its potentiality. However we frequently connect life with freedom. Should the life be a life without freedom or life with freedom, more often to ask, what is the circumference of right? If freedom is to be ascertained as circumferences of right, then this leads to absolutism which can create a chaos and disorder, nonetheless, human right is defined as natural inalienable right, the paradigm is where to place this right, whether within the circumferences of freedom or within the realm of life. Many believe that human right has just a nominal performance in identifying the assimilated galaxy of rights, but the crux of the theory is that human rights has astonishingly surpassed its ability in interpreting and redeeming the justice-right from time to time. Human right as a concept is fundamentally interpreted by the judicial civilization of various countries. These understanding have been unique when interpreting various dimensions of legal rights as well. This research paper attempts to understand the observation of various cultures on human rights and it explores the aspects of human belief system which preaches and propagates the virtuosity of human right. The paper seeks to investigate not just the theoretical spectrum of human right but suggest with a dictum that how impressively the concept can help in redeeming the socio-economic justice to mankind. Cut-crossing the cultural, religious, linguistic and racial difference it makes us to belief that suffering of any one single individual at the corner of world reckons the conscious of mankind; because every man is connect to each other as spirit of one consciousness of being human.